RI 5320 Copper Mines And Prospects Adjacent To Landlocked Bay, Prince William Sound, Alaska ? Summary - Miro Mihelich (The National Institute for Occupational Safety and Health (NIOSH), 1957)
The mines and prospects in the vicinity of Landlocked Bay, 25 miles southwest of Valdez, Alaska (fig. 1), were examined, mapped, and sampled in July and August 1955 as part of a comprehensive investigation by the Bureau of Mines of ore deposits adjacent to Prince William Sound. The purpose of the investigation is to establish and record the location, nature, extent, and metallurgical characteristics of copper and associated metallization in the Prince William Sound district and to indicate, if possible, those areas in which additional exploration and development may be justified. Of particular interest are the possibly numerous deposits of massive iron sulfides that were neglected during early mining operations. These deposits may constitute important reserves of sulfur and iron. At Landlocked Bay deposits of copper-bearing iron sulfide minerals have been mined or partly explored through mine workings, which are in a zone about 1 mile wide along the western side of a large overthrust fault known as the Landlock Overthrust. Eight of the principal mines along this zone were examined end sampled. Although only three of the mines have a recorded production of shipping-grade copper ore, all have deposits of copper-bearing iron sulfide minerals that are similar in occurrence. The deposits occur as lenticular masses and disseminations of chalcopyrite, pyrite, and pyrrhotite which replace crushed rock or fill cavities along shear zones in greenstones and in sedimentary rocks that are exposed between sea level and an altitude of 2,500 feet. These lenticular masses of sulfide minerals range in size from small pods to ore bodies that have been stoped to maximum widths of 9 feet, strike lengths up to 70 feet, and dip lengths as much as 350 feet. Where accessible for sampling,, the copper content of the deposits ranged from a few hundredths of a percent to over S percent; zinc, gold, and silver are present in negligible amounts. Flotation tests of a sample composited to represent typical mine-run ore indicate that 81 percent of the copper is recoverable in a product assaying 28 percent copper at a concentration ratio of 17.5 : 1. INTRODUCTION Statistical records indicate that approximately 110,000 tons of metallic copper (about 16 percent of total Alaskan production) was produced from mines adjacent to Prince William Sound during the 40-year period ended in 1938. Although the principal production was from a large-scale mining and milling operation on Latouche Island (Kennecott Copper Corp., Beatson mine), a substantial amount of the total copper was derived from direct-shipping ores selectively mined or hand-sorted from numerous other deposits in the district. No production has been made since 1938; many of the claims have long been abandoned, and mine workings are either caved or deteriorating rapidly.